EFFECTIVENESS OF THE BANDUNG COMMAND CENTER NTPD 112 SERVICE PROGRAM (SINGLE NUMBER FOR EMERGENCY CALLS) AT BANDUNG CITY COMMUNICATION AND INFORMATION SERVICE - Salsabila, Salma; Ridwan, Muhammad Ridwan (Jurnal Konstituen, 2024)
The use of a single Emergency Call Number 112 which is used as a call center method to report emergencies that occur in the city of Bandung is still less effective. This is based on the fact that there are still many prank calls and ghost calls coming to NTPD 112. This research aims to determine the effectiveness of the Bandung Command Center NTPD 112 service program in emergency calls in Bandung City. Where this research applies effectiveness theory based on the views of M Ricard Steers (1985: 8) who believes that measuring effectiveness can be done through 4 (four) barometers: organizational characteristics, environmental characteristics, worker characteristics, policy characteristics and management practices. The method applied in this research is descriptive with a qualitative approach. Based on the research results, it can be concluded that the Bandung Command Center NTPD 112 service program which is linked to four criteria, namely organizational characteristics, environment, workers and characteristics of management policies and practices, is considered not fully effective. The main problems include double jobs in the Dispatcher division, poor coordination with agencies, low performance ties, the lack of achievement of strategic goals and a lack of innovation which resulted in the number of invalid calls in 2024 for the January-July period being 12,129 incoming calls. Keywords: Effectiveness, Command Center, NTPD 112, Emergency